Pembuatan dan Pembangunan Website di Desa Dagang Kerawan kec. Tanjung Morawa, Kab. Deli Serdang, Sumatera Utara - Indonesia - Surya Darma Nasution; Muhammad Syahrizal; Dito Putro Utomo (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
Seeing the rapid development of science and technology in today's world requires us to keep up with the development of science and technology. Especially in the field of informatics technology such as computers and websites, computers are the most advanced technological development media that are widely used by the general public for processing data with supporting software contained in the computer itself. In this era of globalization, the progress of information technology is very rapid, we can find information easily by utilizing internet facilities. The website is one of the clear evidence of the development of computer technology, where the website is a service that can be accessed by any media. Kerawan Trade Village is a village located in Tanjung Morawa sub-district, Deli Serdang district, North Sumatra province, where in the Kerawan trade village there are several hamlets in it. Many activities are carried out by the people who live in the Kerawan trade village such as youth organizations, UKM activities or products and handicrafts produced by the local community. Every activity, product or handicraft produced should be published to the general public in order to increase the selling value of the Kerawan Trading Village or the sale of products or crafts. Kerawan trading village apparatus has planned the development of rural areas as one of the foundations for village economic growth in the long term by relying on the resources available in the village, one of which is the existence of Village Owned Enterprises (BUMDes). So we need a media called the village website as a place or promotional media about all forms of activities carried out by people who live in the Kerawan trade village. The village website is an online-based portal or site in which there is public information about village activities, both in terms of administrative, social, cultural, institutional and other information related to the village. The implementation team has succeeded in creating and also building a Website for Desa Dagang Kerawan. Village officials and also the people of Dagang Kerawan Village have a website as a medium for promoting activities, products and also crafts produced by the local community. Village officials and also the people of Dagang Kerawan Village can manage and understand the benefits of the website.